Raising Children to Work Hard: Altruism, Work Norms and Social Insurance - Assar Lindbeck; Sten Nyberg (Center for Economic Studies and ifo Institute (CESifo), 2001)
Children who can count on support from altruistic parents may not try hard to succeed in the labor market. Moreover, parental altruism makes withdrawal of such support non-credible. To promote work effort, parents may want to instill norms which later cause their children to experience guilt or shame associated with failure to support themselves. While social insurance pools risk across families, we show that it also creates a free-rider problem among parents in terms of norm formation. We also examine the formation of norms requiring children to support their parents financially in old age.
Keywords: 330; Work norms; social insurance; altruism